POLICY IMPACT OF THE 18TH AMENDMENT ON HEALTH GOVERNANCE AND SERVICE DELIVERY IN PAKISTAN - Irshad Ahmed,; Dr. Zain Rafique, (Journal of Peace, Development and Communication, 2024)
Health governance and healthcare delivery are the key areas of current research. Article 25 of the United Nations Universal Declaration of Human Rights -1948 ensures the right to provision of adequate health facilities to all citizens by all member states. The constitution of World Health Organization effective from April 7, 1948, also ensures physical and mental health with the social well-being of everyone. Good health and well-being is the third Goal set under the 17 Sustainable Development Goals (SDGs) Agenda -2030 by the United Nations global goals by all member states since 2015. For this specific research purpose, rational choice theory was used by adopting Roemer Model of Health Services System Developed by Milton I. Roemer in 1984. Major healthcare models being practiced in the world are Beveridge Model, Bismarck Model, National Health Insurance and medical treatment against cash payment. Beveridge Model is based on the concept of a National Healthcare System with free medical facilities to the public with payment through taxation introduced by Sir William Beveridge in 1942, followed by many commonwealth countries including United Kingdom, New Zealand, Canada, Australia etc. Bismarck Model was introduced by Otto von Bismarck, German Chancellor during his tenure from 1871 to 1890 under which National Health Insurance System was implemented in Germany in 1881 with provision of medical facilities through health insurance companies from designated hospitals against mandatory deductions from employees’ monthly salary. This model was followed in countries like Germany, Japan, South Korea, France etc. The mixture of Beveridge and Bismarck models is called National Health Insurance model under which the public is entitled to get medical treatment from designated hospitals with payment by the government to all concerned health insurance companies. The concept of the out-of-pocket medical expenditure model is based on private medical practice under which patients are getting medical treatment from their choice of doctors and hospitals against payment from their own pocket.